A randomized controlled trial of Mediterranean diet and metformin to prevent age-related diseases in people with metabolic syndrome. Issue 2 (March 2018) - Pasanisi, Patrizia; Gargano, Giuliana; Gaetana Di Mauro, Maria; Cortellini, Mauro; Casagrande, Alice; Villarini, Anna; Bruno, Eleonora; Roveda, Eliana; Saibene, Gabriella; Venturelli, Elisabetta; Berrino, Franco
Purpose: Age-related non-communicable chronic diseases (ArCDs) are the leading cause of mortality. The major metabolic risk factor for their development is the metabolic syndrome (MetS), defined as a clustering of risk factors of metabolic origin such as abdominal obesity, high blood pressure, dyslipidemia and high fasting glycemia. There is increasing observational and experimental evidence that improving diet and the use of metformin (a calorie-restriction mimetic drug) may modify the risk of developing MetS and ArCD. We designed a phase III randomized controlled trial (the Me.Me.Me trial) to evaluate the effect of a comprehensive lifestyle intervention (including moderate physical activity and a Mediterranean-macrobiotic diet) and the effect of treatment with metformin in the prevention of ArCDs in healthy people with MetS. This report describes the scientific protocol of this trial. Methods: The design of the study is 2 × 2 factorial with 2, 000 volunteers to be randomized into 4 equal groups of 500 each, which are allocated to the following treatments: metformin (1, 700 mg/day) + active lifestyle intervention, placebo + active lifestyle intervention, metformin (1, 700 mg/day) alone, and placebo alone. The metformin/placebo component of the study is double blind. The study is planned for a term of 5 years. Results: The Me.Me.Me. trial is ongoing and recruitment of participants is underway. No patient has completed the 5 years of follow-up. Conclusions: We believe that the results of the trial will clarify the importance of lifestyle for primary prevention and the role of metformin as a potential chemopreventive agent. The trial is registred on ClinicalTrials.gov with the identification NCT02960711.